Cost of Illness Analysis in Total Knee Replacement at Public Hospital Jenderal Ahmad Yani, Lampung, Indonesia - Alia, Dina Fatma; Endarti, Dwi; Andayani, Tri Murti (UI Scholars Hub, 2025)
Total knee replacement (TKR) is one of the most economical and frequently successful orthopedic procedures. Cost-of-illness studies of TKR in Indonesia are scarce and lack an analysis of the relationship between characteristics and costs. This study aims to examine the cost-of-illness of TKR from a social perspective and explore the relationship between the characteristics and the cost of TKR. This is an observational cross-sectional study of all patients who underwent TKR from 1st January 2022-31 st December 2023. The characteristics were collected from the medical records. Cost of illness was conducted from a social perspective with a bottom-up approach. Hospital cost on the JKN ECLAIM System was obtained as direct medical cost. Direct non-medical and indirect costs were collected through a phone interview with the patient or caregiver. Indirect cost was defined as income loss from the patient and caregiver. The relationship between characteristics and cost was analyzed bivariately using the Mann–Whitney U test and Kruskal–Wallis test. Of a total 54 patient were obtained. Median direct medical cost was 51,769,675 IDR; direct non-medical cost was 850,000 IDR; and indirect cost was 750,000 IDR. None of the characteristics had a direct relationship with medical cost. Age (p = 0.043), Caregiver (p <0.001), and distance traveled (p <0.001) were known as characteristic related to direct non-medical costs. Indirect cost was related to age (p = 0.053) and employment status (p = 0.005). This study only examined the cost of TKR in the hospital. Costs of post-surgery recovery steps, including costs for revisit consultations, wound care, and physiotherapy, need to be carried out in the future.